An approach to the culture of the English speaking countries through the teaching of English to elementary school students - Cabrera Pérez, Santiago Frank (Universidad de Ciencias Pedagógicas "Félix Varela Morales", 2012)
The present research came out with the purpose of solving a problematic situation caused by the disregard of the potentials offered by the use of an approach to the culture of the English speaking countries in the teaching of the English language to elementary school students. The application of different methods of investigation from the theoretical, empirical and mathematical levels allowed the determination of the theoretical foundations of the research, the assessment of the necessities to meet, and the formulation of the proposal. It come up in the form of a Set of Complementary Didactic Resources whose objective is to facilitate an approach to the culture of the English speaking countries in an interesting, dynamic and motivating way. The specialists consulted gave positive opinions regarding the quality and pertinence of the proposal, and the partial application of the Set of Complementary Didactic Resources in the educative practice proved to be effective among the learners and the educational personnel. Particularly, the impact among the students was very positive, because it opened for them a new universe for knowledge and exchange
Keywords: English; Ingles